Integrin inhibitors in cancer treatment - Rolski, Janusz; Niemiec, Maciej (Contemporary Oncology/Współczesna Onkologia, 2008)
Integrins are the transmembrane proteins involved in intercellular communication and in the contact of cells with extracellular matrix. They are present in healthy and cancer cells as well. They are important in many processes: among other things, thrombosis, angiogenesis and in the metastasis of the neoplastic cells. This article summarizes current knowledge of integrin inhibitors in cancer treatment. All the available studies prove that they have the restrained toxicity and anticancer activity. Introducing them to the standard clinical practice needs further intensive studies.